2004
DOI: 10.1088/0953-8984/16/41/032
|View full text |Cite
|
Sign up to set email alerts
|

Erbia-modified electrospun titania nanofibres for selective infrared emitters

Abstract: Tetraisopropyl titanate (TPT) was mixed with a solution of polyvinylpyrrolidone (PVP) and the solution electrospun into nanofibres. Thermal annealing at 900 • C was used to pyrolyse the PVP, leaving nanofibres of rutile-phase titania. Erbium (III) oxide particles were also added into the solution before electrospinning, and selectively modified the near-infrared optical properties of the titania nanofibres as verified by both absorption and emission spectra. We thereby demonstrate the production of high-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…An example is the conversion of abundant low temperature waste heat into electrical energy in a thermophotovoltaic system [66,67]. Erbium was added to a solution containing tetra-isopropyl titanate and polyvinylpyrrolidone.…”
Section: Ceramic Nanofibersmentioning
confidence: 99%
“…An example is the conversion of abundant low temperature waste heat into electrical energy in a thermophotovoltaic system [66,67]. Erbium was added to a solution containing tetra-isopropyl titanate and polyvinylpyrrolidone.…”
Section: Ceramic Nanofibersmentioning
confidence: 99%
“…The field of electrospinning has witnessed a recent upsurge in interest, particularly involving the production of metal oxide nanofibers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. There has been significant effort on titanium-containing materials systems in our laboratory [4,5,14,17] and others [2,7,16], as well as on fibers formed from aluminum [1,6,18] and zirconium [9,12] precursors.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant effort on titanium-containing materials systems in our laboratory [4,5,14,17] and others [2,7,16], as well as on fibers formed from aluminum [1,6,18] and zirconium [9,12] precursors. However, there are a wide variety of other ceramic nanofibers being produced in laboratories around the world, such as In 3 O 2 [3], WO 3 [8], CuO [10], NaCo 2 O 4 [11], BaTiO 3 [13] and SiO 2 [15], to name only a few.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of solution chemistry and electrospinning procedure have been investigated in some detail, and a recent review 1 summarizes much of this work on nanofibers. [4][5][6][7] Specifically, we are interested in low temperature ͑Ͻ1000°C͒ applications. For example, in a recent study on electrospun titania nanofibers, we found that silicon can be unintentionally introduced into the nanofibers as a result of the solution being in contact with silicone tubing used in the electrospinning apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,7,10 The spectral feature around 6500 cm −1 is relevant for TPV applications which incorporate low band gap photocells ͑e.g., InGaAs or GaSb͒. 4,5,7,10 The spectral feature around 6500 cm −1 is relevant for TPV applications which incorporate low band gap photocells ͑e.g., InGaAs or GaSb͒.…”
Section: Introductionmentioning
confidence: 99%